2009
DOI: 10.1002/ibd.20904
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenterologistsʼ prescribing of infliximab for Crohnʼs disease: A national survey

Abstract: A total of 38% of GIs did not report the use of IM prior to IFX and/or did not use maintenance IFX. GIs practicing outside the Midwest and those in nonacademic settings may need additional training regarding prescribing IFX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Our North American pediatric data are very different from adult surveys of the American Gastroenterological Association in 2009 and of gastroenterologists in Maryland and Washington, DC in 2007, where 70% and 48% of respondents, respectively, said they would use IM prior to prescribing IFX. [ 9 , 10 ]. Similarly, 90% of Swiss adult gastroenterologists reported that they use a conventional step-up strategy, first prescribing thiopurines before using anti-TNF therapy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our North American pediatric data are very different from adult surveys of the American Gastroenterological Association in 2009 and of gastroenterologists in Maryland and Washington, DC in 2007, where 70% and 48% of respondents, respectively, said they would use IM prior to prescribing IFX. [ 9 , 10 ]. Similarly, 90% of Swiss adult gastroenterologists reported that they use a conventional step-up strategy, first prescribing thiopurines before using anti-TNF therapy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A North American survey only assessed previous use of immunomodulators, prescription of maintenance infliximab in CD and knowledge of adverse events. A total of 38% of gastroenterologists did not report the use of immunomodulators prior to infliximab and/or did not use maintenance infliximab therapy 8 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other countries where similar surveys have been performed [7,15,16] , almost all Swedish gastroenterologists (~90%) treat IBD patients with TNF inhibitors. Furthermore, in most hospitals the decision to initiate TNF inhibitors is not taken by the individual physician.…”
Section: O N S U Lt C O Ll E a G U E S A T O T H E R H O S P It A Lmentioning
confidence: 91%